Extrusion tectonics and subduction in the Eastern South Caspian region since 10 Ma - Hollingsworth, J; Jackson, J; Walker, R; Nazari, H (2008)
We examine active deformation of the region surrounding the eastern South Caspian Sea using a combination of seismic, geological, geodetic, and geomorphological data. Global positioning system (GPS) velocities indicate a westward component of motion of the South Caspian basin, relative to Eurasia and central Iran. We identify major zones of shear (the Ashkabad and Shahrud fault zones) that accommodate this westward extrusion on either side of the South Caspian block. Estimates of total strike-slip motion could, at present-day slip rates derived from GPS observations, be achieved in ∼ 10 m.y. Therefore, the northwest extrusion of the South Caspian region, which is accommodated by subduction beneath the North Caspian region (stable Eurasia) along the Apsheron-Balkan sill, may also date from that time. This suggests that the onset of subduction may be older than previous estimates (ranging from 1.8 to 5.5 Ma). Our results are summarized in a new kinematic model that signiticantly clarifies the active tectonics of this complicated region. © 2008 The Geological Society of America.